EFEKTIVITAS PENGGUNAAN VIDEO PEMBELAJARAN TERHADAP KEBERHASILAN BELAJAR SISWA PADA MATA PELAJARAN PAI DI SMP MA’ARIF 02 MALANG - Nur Aini Khosimah; Qurroti A’yun; Mutiara Sari Dewi (VICRATINA, 2022)
This study intends to determine the effectiveness of the use of learning videos on student learning success in pie subjects at SMP Ma'arif 02 Malang. The research used is a quasi-experimental method in the form of research using pretest and posttest. The results of the study prove the effect of using audio-visual learning media (learning videos) on student learning outcomes. The results showed that the use of audio-visual learning media was considered effective enough to improve student learning outcomes. This can be seen from t count > t table (11.496 > 0.68581) which proves the influence of independent variables on the dependent variable.